A unique Y gene in the Asian malaria mosquito Anopheles stephensi encodes a small lysine‐rich protein and is transcribed at the onset of embryonic development. Issue 4 (20th May 2013) - Criscione, F.; Qi, Y.; Saunders, R.; Hall, B.; Tu, Z.
Abstract In many organisms the Y chromosome initiates sex determination and regulates male fertility and mating behaviour. However, molecular characterization of Y genes is rare outside of a few model species because it is difficult to clone and analyse repeat‐rich heterochromatic Y sequences. In insects, Y genes are only well characterized in a small number of Drosophila species. Here we report the discovery of GUY1 (gene unique to the Y), a gene unique to the Y chromosome in the Asian malaria mosquito, Anopheles stephensi, using an approach that compares Illumina sequences separately obtained from male and female genomic DNA. Experimental evidence confirmed that GUY1 is a single copy gene found only on the Y chromosome. GUY1 is transcribed at the very onset of zygotic transcription and encodes a small lysine‐rich protein that forms two alpha helices and shows DNA‐binding properties. Interestingly, three helix‐loop‐helix proteins are key factors that determine sex in the early embryo in Drosophila melanogaster. Single embryo analysis indicated that GUY1 is only transcribed in male embryos and that the GUY1 promoter is functional in the early embryos. GUY1 may be used as a paternally inherited molecular marker. Further investigation of GUY1 will contribute to the genetic approaches to control mosquito‐borne diseases.